Providing Medication Instruction to an Older Adult Caregiver - Kathryn Hines; Amanda Soong (Association of American Medical Colleges, 2012)
Abstract In this case, a 4-year-old child is brought to the primary care clinic by his older adult caregiver with a chief complaint of "breathing problems." The child has a history of asthma, and the older adult caregiver is no longer giving him his medicines as prescribed. The older adult caregiver is also experiencing various issues associated with normal aging, such as hearing loss, visual changes, and mild cognitive changes. It is the learner's job to determine that the medicines are no longer being administered properly and educate the caregiver on how to properly administer the child's medications. The purpose of the case is to not only to train learners how to provide asthma education but to also increase their awareness of older adult caregivers and the barriers to effective communication with this population. This simulation case is an effective tool for teaching learners how to provide medication instruction and effectively communicate with an older adult caregiver. Studies report high rates of noncompliance with asthma medication regimens, and pediatricians should feel comfortable addressing barriers to medication compliance. They should also feel comfortable using a number of methods to ensure that caregivers understand how to properly administer medications. In today's society, an increasing number of children are being raised in households headed by someone other than a biological parent. A large portion of children are being raised by grandparents or other older adult caregivers. Pediatricians need to feel comfortable communicating with and addressing the needs of this unique caregiver population. The authors believe that this resource will raise awareness among learners regarding the prevalence of older adult caregivers and increase learners' comfort level in addressing the unique needs of these caregivers. This case has been performed six discrete times at the authors' institution, and all participants surveyed thought the case and debriefing sessions were valuable learning experiences.